Penerapan Model Garch Untuk Menguji Efisiensi Pasar Bentuk Lemah - Eka Yulianti; Dwi Jayanti (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this study is to determine whether returns follow a random pattern and test the market efficiency of a weak form using ARCH-GARCH. The population in this study is all shares that are incorporated in the Kompas 100 index group on the Indonesia Stock Exchange with a sample used in this study amounting to 83 shares using purposive sampling technique. The analysis technique used in applying the GARCH model in this study uses the help of the Eviews 8 program software. The results of this study are that the movement of returns follows a random pattern during the 2015-2018 period, the efficient market is in a weak form during the 2015-2018 period, so investors do not can use stock movement data in the past for consideration of investment.